Gender differences in tournament choices: Risk preferences, overconfidence or competitiveness? - Roel van Veldhuizen (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2017)
A large number of recent experimental studies show that women are less likely to sort into competitive environments. While part of this effect may be explained by gender differences in risk attitudes and overconfidence, previous studies have attributed the majority of the gender gap to gender differences in a separate 'competitiveness' trait. We re-examine this result using a novel experimental technique that allows us to separate competitiveness from alternative explanations by experimental design. In contrast to the literature, our results imply that the whole gender gap is driven by risk attitudes and overconfidence, which has important implications for future research.
Keywords: C90; J16; D03; 330; gender; competitiveness; lab experiment; experimental design